Ultrastructural evidence for the accumulation of insulin in nuclei of intact 3T3-L1 adipocytes by an insulin-receptor mediated process. - Smith, R M (1987)
Monomeric ferritin-labeled insulin (Fm-Ins), a biologically active, electron-dense marker of occupied insulin receptors, was used to characterize the internalization of insulin in 3T3-L1 adipocytes. Fm-Ins bound specifically to insulin receptors and was internalized in a time- and temperature-dependent manner. Fm-Ins was found in cytoplasmic vesicles within 5-10 min at 37 degrees C and subsequently was observed in multivesicular bodies and lysosomes. In addition, small amounts of Fm-Ins were associated with nuclei after 30 min. The number of Fm-Ins particles observed in nuclei continued to increase in a time-dependent manner until at least 90 min. In the nucleus, several Fm-Ins particles usually were found in the same general location--near nuclear pores, associated with the periphery of the condensed chromatin. Addition of a 250-fold excess of unlabeled insulin or incubation at 15 degrees C reduced the number of Fm-Ins particles found in nuclei after 90 min by 99% or 92%, respectively. Nuclear accumulation of unlabeled ferritin was only 2% of that found with Fm-Ins after 90 min at 37 degrees C. Biochemical experiments utilizing 125I-labeled insulin and subcellular fractionation indicated that intact 3T3-L1 adipocytes internalized insulin rapidly and that approximately equal to 3% of the internalized ligand accumulated in nuclei after 1 hr. These data provide biochemical and high-resolution ultrastructural evidence that 3T3-L1 adipocytes accumulate potentially significant amounts of insulin in nuclei by an insulin receptor-mediated process. The transport of insulin or the insulin-receptor complex to nuclei in this cell or in others may be directly involved in the long-term biological effects of insulin--in particular, in the control of DNA and RNA synthesis.